Strike at Smithfield's Meat market fot higher wages and better conditions. Because of the meat shortage meat has to be imported from Argentina and more fish has to be delivered. Series of 2 photos
Strike at Smithfield's Meat market fot higher wages and better conditions. Because of the meat shortage meat has to be imported from Argentina and more fish has to be delivered. Series of 2 photos.